Analysis of tribo-charging during powder spreading in selective laser sintering: Assessment of polyamide 12 powder ageing effects on charging behavior - Hesse, Nicolas; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Lübbert, Christian; Roth, Stephan; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2019)
Powder flowability is key to achieving high process stability and part quality by application of smooth and dense layers in selective laser sintering (SLS). This study sheds light on the rarely investigated effect of tribo-electric charge build-up during powder delivery in the SLS process. This is achieved by a novel approach to quantify electrostatic potentials during doctor blading. The presented model setup is used in combination with charge spectrometry and impedance spectroscopy to investigate the alterations in tribo-electric charging behavior for the most commonly used laser sintering material polyamide 12 in its virgin and aged, c.f. reused, states. We show that the electrostatic charge build-up is significantly enhanced for aged polymer powder material, likely contributing to altered performance in SLS processing.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Additive manufacturing; Charge distribution; Electrostatics; Polyamide 12; Polymer ageing; Powder layer formation; Selective laser sintering; Surface potential; Tribo-charging